1986
DOI: 10.1093/carcin/7.11.1899
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the carcinogenicity of fusarin C — a mutagenic metabolite of Fusarium moniliforme

Abstract: The cancer initiating potential of fusarin C, a mutagen produced by Fusarium moniliforme strain MRC 826 was investigated on mouse skin using 12-O-tetradecanoylphorbol-13-acetate as promoter. In neither of these models did fusarin C act as a cancer initiator. Culture material of strain MRC 826, which previously was found to be hepatocarcinogenic in rats, exhibited cancer promoting activity in rat liver using diethylnitrosamine (DEN) as initiator and the induction of gamma glutamyltranspeptidase (GGT)-positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 0 publications
5
44
0
Order By: Relevance
“…This involved partial hepatectomy of rats, followed by administration of an initiator such as diethylnitrosamine (DEN), followed by administration of a promotor such as phenobarbital. After 14 weeks, the gamma glutamyltranspeptidase (GGT) activity was determined histochemically in the liver (2,20,22). During the application of this short-term carcinogenicity assay, it was found that culture material of F. verticillioides MRC 826 initiated the formation of early lesions in the liver and exhibited cancer-promoting activity.…”
Section: Events Leading To the Characterization Of The Fumonisins In mentioning
confidence: 99%
“…This involved partial hepatectomy of rats, followed by administration of an initiator such as diethylnitrosamine (DEN), followed by administration of a promotor such as phenobarbital. After 14 weeks, the gamma glutamyltranspeptidase (GGT) activity was determined histochemically in the liver (2,20,22). During the application of this short-term carcinogenicity assay, it was found that culture material of F. verticillioides MRC 826 initiated the formation of early lesions in the liver and exhibited cancer-promoting activity.…”
Section: Events Leading To the Characterization Of The Fumonisins In mentioning
confidence: 99%
“…The isolation and characterization of fumonisins is relatively recent [90]. Fumonisins are a family of water-soluble toxins produced by different strains of Fusarium verticillioides (moniliforme) and F. proliferatum.…”
Section: Fumonisinsmentioning
confidence: 99%
“…Another prominent lesion was the concurrent development of cholangio-or adenofibrosis, a lesion that appears to develop from the proliferation of hyperplastic epithelial cells, goblet cells, and Paneth cells. The experiment was conducted with both oven-dried (MRC 826, batch [9][10][11][12][13][14][15][16][17][18][19][20] and freeze-dried (MRC 826, batch B) culture material and identical lesions were induced; however, the degree of the effects was higher with the freeze-dried material. It was suggested that the causative principle(s) was partially destroyed during the ovendrying treatment at 45-50°C.…”
Section: Studies With Cultures Of F Verticillioides Strain Mrc 826mentioning
confidence: 99%
“…This study further strengthened the hypothesis that the causative toxic principle(s) responsible for ELEM in horses and the hepatotoxicity/carcinogenicity in rats could be identical. Studies of the carcinogenic effects of fusarin C in a short-term cancer initiation/promotion model indicated that culture material of F. verticillioides strain MRC 826 exhibited cancer-promoting activity when using diethylnitrosamine (DEN) as a cancer initiator and the induction of GGT-positive foci and/or nodules as end points (12). Subsequently, several other strains of the fungus, isolated from a high-incidence area of esophageal cancer in Transkei, were screened for cancer-promoting activity in a modified version of the resistant hepatocyte rat liver model (13).…”
Section: Studies With Cultures Of F Verticillioides Strain Mrc 826mentioning
confidence: 99%